2021
DOI: 10.1155/2021/2527595
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors of Restroke in Patients with Lacunar Cerebral Infarction Using Magnetic Resonance Imaging Image Features under Deep Learning Algorithm

Abstract: This study was aimed to explore the magnetic resonance imaging (MRI) image features based on the fuzzy local information C-means clustering (FLICM) image segmentation method to analyze the risk factors of restroke in patients with lacunar infarction. In this study, based on the FLICM algorithm, the Canny edge detection algorithm and the Fourier shape descriptor were introduced to optimize the algorithm. The difference of Jaccard coefficient, Dice coefficient, peak signal-to-noise ratio (PSNR), structural simil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…It was inappropriate to use Euclidean distance in this case, so the kernel function was introduced to measure the distance between pixels in the space. The low-dimensional space was mapped to the high-dimensional space, and the complex nonlinear issue was transformed into the linear issue of kernel space [ 13 , 14 ], enhancing the noise immunity of the algorithm. The steps of improving the FCM algorithm were given as follows.…”
Section: Methodsmentioning
confidence: 99%
“…It was inappropriate to use Euclidean distance in this case, so the kernel function was introduced to measure the distance between pixels in the space. The low-dimensional space was mapped to the high-dimensional space, and the complex nonlinear issue was transformed into the linear issue of kernel space [ 13 , 14 ], enhancing the noise immunity of the algorithm. The steps of improving the FCM algorithm were given as follows.…”
Section: Methodsmentioning
confidence: 99%
“…The results showed that, under the same noise conditions, the optimized FLICM algorithm exhibited higher Jaccard coefficient, Dice coefficient, PSNR, and SSIM values when segmenting brain tissue compared to other algorithms. Additionally, age and a history of hypertension were identified as risk factors for recurrent stroke after lacunar infarction ( 86 ).…”
Section: Progress In Predicting the Rehabilitation Of Ischemic Stroke...mentioning
confidence: 99%
“…Compared to computed tomography (CT) scans, MRI scans offer greater sensitivity, and many imaging features can only be detected through MRI. 2 Notably, there are multiple radiological markers for CSVD, including white matter hyperintensities (WMH), recent small subcortical infarcts (RSSI), lacunar infarcts (LI), enlarged perivascular spaces (EPVS), and cerebral microbleeds (CMB). 3 Different imaging markers rely on different MRI sequences for detection.…”
Section: Introductionmentioning
confidence: 99%